Microgeometrical characteristics of electrospark coatings in the initial state - Tokaruk, V.V.; Mikosianchyk, O.O.; Mnatsakanov, R.G.; Rohozhyna, N.O. (Problems of Tribology, 2020)
Microgeometric parameters of the effect of discrete electrospark coatings on their stress-strain state have been evaluated for the case of using a combined technology of modification of duralumin D16, which includes the technique of electrospark alloying with subsequent surface plastic deformation of coatings formed. According to the profilograms of discrete electrical coatings, the curves of the bearing surface (Abbott curves) were constructed and the parameters that drastically affect tribological characteristics of the coatings were determined. It was shown that modification of duralumin D16 with a combined electrospark coating VK-8 + Cu reduces the arithmetic mean height of peaks in the top portion of the profile by 4.4 and 3.2 times, doubles the arithmetic mean depth of the profile core irregularities, increases the arithmetic mean depth of profile valleys by 1.8 and 1.1 times, in comparison with electrospark coatings from hard alloy VK-8 and copper, respectively. These parameters help to reduce the period of running-in of the contact surfaces strengthened by the combined electrospark coating VK-8 + Cu, increase their bearing capacity, contact durability and specific oil consumption. On the basis of the finite element analysis method of the Nastran software complex, a model of the stress-strain state of a discrete coating/base was designed and distribution of the main normal stresses was determined for a coating compactness of 60% under a normal load of 600 N. The performed modeling revealed advantages of a combined technology for formation of wear-resistant electrospark coatings, which consists in turning residual tensile stresses into compressive ones. When modifying the duralumin D16 with a VK-8 + Cu coating, on the coating surface and in the base material, compressive stresses (-93 MPa and -20 MPa, respectively) are formed, which provides a decrease in wear of the modified surface by two times compared to unmodified duralumin D16.